Evaluation of sustainable supply chain performance on apple chips using the integration of quality function deployment, fuzzy analytical network process, and data envelopment analysis - Awal Ramadan; Wike Agustin Prima Dania; Siti Asmaul Mustaniroh (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Batu City is the largest apple producer in Indonesia, producing around 55,891 tons. One way to optimize supply chains is sustainable supply chain performance in the economic, social, and environmental fields. Problems in apple chip small- and medium-scale enterprises (SMEs) are the price of apples increases in the dry season, accumulation of apple peel waste, and poor employee work performance. This study aimed to analyze the level of importance variables in measuring the supply chain performance level and the strategies to improve the supply chain of apple chips SMEs in Batu City. The integration of quality function deployment (QFD) and Fuzzy analytical network process (FANP) was used to obtain the level of cooperation interest. Data envelopment analysis (DEA) was used to determine the efficiency of each stakeholder's interest. The results showed that the three highest important cooperative behavior factors were production costs (0.16), raw material costs (0.15), and raw material inventory (0.14). The efficiency level of partner cooperation and apple chip SMEs from 17 SMEs indicated that two partners were inefficient, with an efficiency score of 0.973 (D3) and 0.957 (D4). The improvement strategies proposed to apple chip SMEs were reducing production costs, revising agreements between suppliers and farmers, and implementing information technology.